Gamified Learning in Remote Junior High Schools in Gowa Regency: Teacher Perceptions on its Role in Vocabulary Acquisition and Motivation - Asni Suryaningsih; Goestina Goestina (Institute of Multidisciplinary Research and Community Service, 2024)
Abstract: This study explores the perceptions of junior high school teachers in remote areas regarding the use of gamified learning environments (GLEs) in enhancing vocabulary acquisition and fostering student motivation. Specifically, the research focuses on the application of Word wall, an interactive gamified tool that allows educators to create customizable vocabulary games. A mixed- methods approach was employed, combining quantitative surveys and qualitative semi-structured interviews with 30 language teachers from remote junior high schools. The results of the survey indicated that 85% of teachers found Word wall effective in supporting vocabulary acquisition, while 90% observed increased student motivation when using gamified learning activities. Teachers reported that the engaging and interactive nature of the games, including quizzes, matching games, and word searches, helped students better retain vocabulary. However, challenges such as limited access to technology, insufficient teacher training, and inconsistent student engagement were identified as barriers to fully utilizing gamified learning tools. The study concludes by recommending the provision of professional development for teachers, improvements in technological infrastructure, and a more personalized approach to gamified learning to maximize its effectiveness in remote educational settings. Keywords: gamified learning, vocabulary acquisition, student motivation, remote junior high schools, teacher perceptions.